Grumiplucite from the Rudnany deposit, Slovakia: a second world-occurrence and new data - Stevko,M.; Sejkora,J.; Peterec,D. (Journal of Geosciences, 2015)
Grumiplucite, ideally HgBi2S4 was identified at the Drozdiak vein, Rudnany deposit (Spissko-gemerske Rudohorie Mts., Slovakia). This rare Hg-sulfosalt forms metallic lead-grey to steel-grey, prismatic to acicular crystals up to 1 cm long, often grouped into irregular aggregates. It occurs in cavities of siderite with abundant cinnabar, Hg-rich tetrahedrite and chalcopyrite aggregates. Minor quartz or barite crystals and microscopic aggregates of Sb-rich bismuthinite to Bi-rich antimonite were also observed. On the basis of chemical analyses, two types of grumiplucite were distinguished at the Rudnany deposit. The first is close to an ideal composition and has empirical formula Hg0.99Bi1.94S4.08 (based on 7 apfu). The second is characterized by regularly elevated contents of Sb ranging from 0.02 to 0.77 apfu. Grumiplucite is monoclinic, space group C2/m with unit-cell parameters refined from X-ray powder data: a = 14.172(2), b = 4.0525(7), c = 13.975(1) Å, β = 118.257(8)o and V = 707.0(2) Å3 (Sb-free) and a = 14.183(1), b = 4.0538(5), c = 13.980(1) Å, β = 118.239(1)o and V = 708.1(2) Å3 (Sb-rich). Raman spectra for grumiplucite crystals with variable Sb contents are mutually well comparable. Therefore it seems that different Sb occupation does not affect to energy and intensity of Raman bands and they significantly differ from spectra of particularly structure-related mineral livingstonite, HgSb4S8. The dominant feature in the Raman spectra of grumiplucite is a series of spectral bands that corresponds to the stretching and bending vibrations of BiS5 polyhedra and Hg-S bonds.
Keywords: grumiplucite; sulfosalts; X-ray powder data; chemical composition; Raman spectroscopy; Rudnany deposit